Longitudinal Changes of Macular Curvature in Patients with Retinitis Pigmentosa - Meinert, Monika (Transl Vis Sci Technol, 2020)
PURPOSE: To investigate the longitudinal changes of the macular curvature in eyes with retinitis pigmentosa (RP) and to determine the factors associated with the changes. METHODS: We reviewed the medical charts of 107 RP patients, for whom the axial length of their right eyes ranged from 21.5 to 26.0 mm and who had had been followed by spectral-domain optical coherence tomography (OCT). The OCT images at the initial and the most recent examinations were compared. The mean curvature of Bruch's membrane within 6 mm of the central macula obtained from the OCT images was evaluated as the mean macular curvature index (MMCI). Changes in the MMCI and their relationships with other clinical factors, including the ellipsoid zone (EZ) width, were assessed. RESULTS: The MMCI decreased significantly in the vertical OCT images, from –15.47 × 10(−5) µm(−1) to –16.36 × 10(−5) µm(−1) (P = 0.008) during the mean observation period of 3.4 ± 1.4 years (mean ± SD). This indicated that the macular shape became more concave. The change to a steeper shape was more prominent in eyes with less photoreceptor degeneration and for which the EZ width was preserved at >2000 µm. In three eyes, the MMCI increased markedly by >5 × 10(−5) µm(−1), and this was accompanied by absorption of the macular edema. CONCLUSIONS: The macular curvature in RP eyes becomes more concave in eyes with preserved EZ width. TRANSLATIONAL RELEVANCE: Longitudinal changes of the macular curvature in RP should be considered in future therapies, such as the implantation of the retinal prosthesis.